Making Space for Failure in the Scholarship of Teaching and Learning: A Blueprint - Chick, Nancy L.; Cruz, Laura; Friberg, Jennifer C.; Steiner, Hillary H. (Teaching and Learning Inquiry, 2023)
In this essay, we offer a typology of failure in the scholarship of teaching and learning (SoTL) to serve as the foundation for a new line of inquiry to be featured in this new section of Teaching & Learning Inquiry — SoTL in Process. Through the typology, we advocate for making space to talk about failure and its many forms in SoTL. Read the corresponding ISSOTL blog post here.